Treatment of Advanced Seminoma with Dactinomycin, Cyclophosphamide, Vinblastine, Bleomycin and Cis-Platinum (The Vab-6 Protocol) - Sergio D. Simon; Miguel Srougi (Revista Brasileira de Cancerologia, 2023)
Eighteen patients with advanced seminoma (stages llc— III) were treated with: cytoxan 600mg/m2, vinblastine 4mg/m2, actinomycin D 1mg/m2, bleomycin 30mg, i.v. on day 1, followed by bleomycin 30mg/day by infusion, days 1-3, and cis-platinum 120mg/m2 on day 4. 9/18 pts. Achieved complete remission and have been followed clinically; no recurrences have occurred in this group. The other 9 pts. had residual masses after 3 cycles of chemotherapy; they were taken to surgery and no viable tumor was found on surgical specimens. There were 3 recurrences in this group, always distant from the site of original disease. These patients were successfully treated with salvage chemotherapy and radiotherapy. One of these patients died of hepatic failure unrelated to his seminoma. All the other patients are alive, at a median follow-up of 50 months. This chemotherapy regimen is effective in curing advanced seminoma.